2009
DOI: 10.1007/s10570-009-9279-z
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing behaviour of lyocell fabric: effect of NaOH pre-treatment

Abstract: To understand the effect of alkali pretreatment on the dyeing of lyocell fabrics, samples are pre-treated with 0.0-7.0 mol dm -3 NaOH using a pad-batch process and then dyed with different types of reactive dyes. Exhaustion, fixation, and visual colour strength (K/S values) are measured. It is observed that sodium hydroxide pre-treatment significantly improves the colour yield, exhaustion, and fixation for all dyes used. Highest K/S values are obtained when the fabrics are pre-treated with 2.0-2.5 mol dm -3 Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…However, from an industrial perspective the findings will enable dyehouses to achieve a higher depth of shade on lyocell by pre-treatment of the substrate; the optimum concentration to achieve highest sorption is 2.0 mol dm -3 NaOH. This work compliments our previous research (Goswami et al 2009b) where it was also observed that highest visual colour yield is achieved when lyocell was pre-treated with 2.0 mol dm -3 NaOH.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, from an industrial perspective the findings will enable dyehouses to achieve a higher depth of shade on lyocell by pre-treatment of the substrate; the optimum concentration to achieve highest sorption is 2.0 mol dm -3 NaOH. This work compliments our previous research (Goswami et al 2009b) where it was also observed that highest visual colour yield is achieved when lyocell was pre-treated with 2.0 mol dm -3 NaOH.…”
Section: Discussionsupporting
confidence: 91%
“…The work concluded that formation of Na-cellulose II causes plasticization of the lyocell fibre as both inter-and intra-molecular hydrogen bonds are broken by these higher sodium hydroxide concentrations. We have also observed previously using reactive dyes that NaOH pre-treatment significantly improves the colour yield, exhaustion, and fixation of lyocell fabric (Goswami et al 2009b), and that an understanding of reactive dyeing of lyocell is particularly important in relation to fibrillation properties of lyocell (Goswami et al 2007), which can be affected by NaOH treatment. The purpose of the work reported herein is to gain a deeper understanding of the sorption system involved when cellulose II fibres (lyocell) are pre-treated with aqueous sodium hydroxide solution, and how this affects sorption of dye molecules of varying molecular size.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It has been reported that swelling of lyocell and modal fabrics causes the expansion of void spaces within the semi-crystalline morphology, thus forming a water fiber two phase structure (7,17,18) . The expansion of internal structure leads to a very high internal wetted surface area, meaning that a high proportion of the polymer hydroxyl groups become accessible to the swelling medium.…”
Section: Effect Of Swelling Agents On the Dyeabilitymentioning
confidence: 99%
“…Although results regarding the dyeability of lyocell and modal fabrics with reactive and direct dyes have been published (5)(6)(7) , a detailed study of the effect of pre-swelling in metal salts on their dyeability with reactive and direct dyes has not appeared.…”
mentioning
confidence: 99%